Implementation of Lean Six Sigma in Improving Quality by Reducing Defective Products in Aqua Mineral Water Gallon Distribution - Rusindiyanto; Isna Nugraha; Friska Aryanti (Nusantara Science and Technology Proceedings, 2024)
Surya Galon Agent is one of the gallon agents in Sidoarjo. The gallon product that is in great demand is the AQUA gallon. The problem faced is the high number of defects. This research aims to identify the types of defects that cause high levels of weekly defects for one year, determine the factors that influence the quality of AQUA mineral water gallon products at Galon Surya Agent, analyze the main causes of each type of defect and provide suggestions for improvement using the Lean Six Sigma approach. The Lean Six Sigma method seeks to integrate Lean manufacturing principles with Six Sigma. From the total number of gallons of AQUA mineral water products totaling 5720 units, the number of damaged units was 220 units. From research that has been calculated, the DPMO result is 1282 with a sigma level of 3.73. These results show that quality control for AQUA gallon mineral water products still requires improvement to minimize the number of defects. Analysis of SQCDMPE (Safety, Quality, Cost, Delivery, Moral, Productivity, Environment) is Improved monitoring of raw materials; Reduction in defect rate from 3.73 sigma to 4.01 sigma, an increase of 0.28 sigma; Decrease in repair costs through quality control; Improvement in timely delivery of products to consumers, reducing customer complaints; Increased employee satisfaction and motivation through training programs and rewards; Increased productivity due to process improvements and more regular machine maintenance; Reduction in environmental impact through better waste management and use of more eco-friendly raw materials.